Assessment of Critical Infrastructure Within the National Mining Subsector - Daniel Nicolae Fita; Mila Ilieva Obretenova; Sorina Daniela Stanila; Adriana Zamora; Safta Gheorghe Eugen; Florin Grecu-Muresan (Advances and Challenges in Science and Technology Vol. 3, 2023)
Mining industry is one of the most important industrial sectors for different countries, especially those that are drastically dependent on their available mining resources. Mining industry refers to the cluster of clusters of industries related to the mining related activities, that is, extraction, refining, and so on. Unlike many other large industrial setting, this industrial sector is comparatively small, but it involves the generation of very hazardous materials as by-products and as waste materials. The necessity to evaluate security threats on the national mining subsector, which produces and possesses vital mining infrastructures, arises in the context of the potential occurrence of energy blackout situations, which raises significant questions of national interest and has ramifications for Europe and NATO. Critical mining infrastructures must be extensively analyzed in terms of ensuring and increasing energy and national security in order to avert possible national crises since they may be exposed to internal and/or foreign attacks. The shortage of coal or the power generated by it may severely harm industry, the economy, and state structures, which are virtually exclusively dependent on electricity, according to the authors, who feel that addressing the national mining subsector is a purely national security problem.